Reciprocity in organisations: Evidence from the UK - Florian Englmaier; Thomas Kolaska; Stephen Leider (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
Recent laboratory evidence suggests that personality traits, in particular social preferences, may affect contractual outcomes under moral hazard. Using the British Workplace Employment Relations Survey 2004 we find that behaviour of employers and employees is consistent with the presence of gift-exchange motives: firms that screen applicants for personality are less likely to pay low wages and more likely to provide (non-pecuniary) benefits. Firms likewise benefit from employee screening as they can implement more team-working and are generally more successful. Other human resource management practices only poorly predict these patterns. Moreover, there is no association between dismissals and personality tests, indicating that personality tests do not merely improve the fit between applicant and employer. Hence, we conclude that motivation based on gift-exchange motives is a plausible explanation for our results.
urn:nbn:de:bvb:19-epub-24876-4
Keywords: D22; M52; 330; Reciprocity; Organisational Structure; Employee Compensation